2020
DOI: 10.1038/s41598-020-62060-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Antagonistic Effects of Aromatics on the Agglomeration of Gas Hydrates

Abstract: Surfactants are often used to stabilize aqueous dispersions. For example, surfactants can be used to prevent hydrate particles from forming large plugs that can clog, and sometimes rupture pipelines. Changes in oil composition, however dramatically affect the performance of said surfactants. In this work we demonstrate that aromatic compounds, dissolved in the hydrocarbon phase, can have both synergistic and antagonistic effects, depending on their molecular structure, with respect to surfactants developed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The headgroup including both the amide and tertiary ammonium cation group is known for its ability to adsorb on the hydrate surface. [20][21][22][23] The two long R 1 tails are composed of a linear hydrocarbon of twelve carbon atoms with an aromatic ring (benzene) positioned either at the bottom (Fig. 2b) or in the middle (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The headgroup including both the amide and tertiary ammonium cation group is known for its ability to adsorb on the hydrate surface. [20][21][22][23] The two long R 1 tails are composed of a linear hydrocarbon of twelve carbon atoms with an aromatic ring (benzene) positioned either at the bottom (Fig. 2b) or in the middle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, small changes in the molecular structure of the surfactants can strongly affect their ability to prevent hydrate plug formation. 23 Phan et al showed that the adhesion of AAs on hydrate particles is strongly dependent on the molecular features of the AA headgroups, thus explaining the experimental observations. 19 Trout and his group showed that the adhesion between monomers and hydrate surfaces is related to the performance of kinetic hydrate inhibitors, 24 and recent results show that the adsorption of AAs at the hydrate-water interface is strongly affected by the presence of salts in the system.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations